Enhanced pulmonary leptin expression in patients with severe COPD and asymptomatic smokers. Issue 1 (3rd October 2008) - Vernooy, J H J; Drummen, N E A; van Suylen, R J; Cloots, R H E; Möller, G M; Bracke, K R; Zuyderduyn, S; Dentener, M A; Brusselle, G G; Hiemstra, P S; Wouters, E F M
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is characterised by an abnormal inflammatory reaction of the lungs involving activation of epithelial cells. Leptin is a pleiotropic cytokine important in the regulation of immune responses via its functional receptor Ob-Rb. This study was undertaken to test the hypothesis that severe COPD is associated with increased leptin expression in epithelial cells. Methods: Immunohistochemistry for leptin was performed on peripheral lung specimens from 20 patients with COPD (GOLD stage 4), 14 asymptomatic ex-smokers and 13 never smokers. Leptin and Ob-Rb mRNA expression were determined by rtPCR in cultured primary bronchial epithelial cells and primary type II pneumocytes. NCI-H292 and A549 cell lines were used to study functional activation of leptin signalling. Results: Leptin immunoreactivity in lung tissue was observed in bronchial epithelial cells, type II pneumocytes, macrophages (tissue/alveolar) and interstitial lymphocytic infiltrates. rtPCR analysis confirmed pulmonary leptin and Ob-Rb mRNA expression in primary bronchial epithelial cells and pneumocytes. Leptin-expressing bronchial epithelial cells and alveolar macrophages were markedly higher in patients with severe COPD and ex-smokers than in never smokers (p<0.02). Exposure of cultured primary bronchial epithelial cells to smoke resulted in increased expression of both leptin and Ob-Rb (p<0.05). Leptin induced phosphorylation of STAT3 in both NCI-H292 and A549 cells. Conclusions: Leptin expression is increased in bronchial epithelial cells and alveolar macrophages of ex-smokers with or without severe COPD compared with never smokers. A functional leptin signalling pathway is present in lung epithelial cells.